An Intracellular Pathway Controlled by the N-terminus of the Pump Subunit Inhibits the Bacterial KdpFABC Ion Pump in High K+ Conditions. Issue 15 (23rd July 2021) - Dubey, Vikas; Stokes, David L.; Pedersen, Bjørn Panyella; Khandelia, Himanshu
Graphical abstract: Highlights: Phosphorylation of the TGES motif regulates the ion-transporting protein KdpFABC. Our MD simulations show that phosphorylation hydrates the pump ion-binding site. We postulate that the hydrated state is a trapped inactive conformation of KdpFABC. The pump N-terminus controls access to the pathway leading to the ion-binding site. Phosphorylation of the TGES motif is allosterically coupled to N-terminus dynamics. Abstract: The heterotetrameric bacterial KdpFABC transmembrane protein complex is an ion channel-pump hybrid that consumes ATP to import K + against its transmembrane chemical potential gradient in low external K + environments. The KdpB ion-pump subunit of KdpFABC is a P-type ATPase, and catalyses ATP hydrolysis. Under high external K + conditions, K + can diffuse into the cells through passive ion channels. KdpFABC must therefore be inhibited in high K + conditions to conserve cellular ATP. Inhibition is thought to occur via unusual phosphorylation of residue Ser162 of the TGES motif of the cytoplasmic A domain. It is proposed that phosphorylation most likely traps KdpB in an inactive E1-P like conformation, but the molecular mechanism of phosphorylation-mediated inhibition remains unknown. Here, we employ molecular dynamics (MD) simulations of the dephosphorylated and phosphorylated versions of KdpFABC to demonstrate that phosphorylated KdpB is trapped in a conformation where the ion-binding site is hydrated by an intracellular pathway between transmembrane helices M1 and M2 which opens in response to the rearrangement of cytoplasmic domains resulting from phosphorylation. Cytoplasmic access of water to the ion-binding site is accompanied by a remarkable loss of secondary structure of the KdpB N-terminus and disruption of a key salt bridge between Glu87 in the A domain and Arg212 in the P domain. Our results provide the molecular basis of a unique mechanism of regulation amongst P-type ATPases, and suggest that the N-terminus has a significant role to play in the conformational cycle and regulation of KdpFABC.